2020
DOI: 10.1021/acssuschemeng.9b07600
|View full text |Cite
|
Sign up to set email alerts
|

Cardanol- and Guaiacol-Sourced Solution-Processable Green Small Molecule-Based Organic Solar Cells

Abstract: An environmentally compatible organic solar cell (OSC) has potential to build a global clean energy infrastructure for the world. However, much less attention has been focused on the structures sourced from greener origins to enhance the sustainability aspect of these devices. Herein, we report a rational design, synthesis, and characterization of donor (D)-acceptor (A)based green organic small molecules, consisting of difluoro-2,1,3benzothiadiazole (BTF 2 ) as the acceptor, with thiophene (T) and renewable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The small molecule donor (SMD) designed as D-A-D configuration consisting of difluroro-2,1-3-benzothiadiazole as the acceptor and dialkoxyphenyl-thiophene-based terminal donor units containing a lignin sourced phenol, guaiacol as the end groups. [55] This is used as third component in the P:Y6-based ternary OSCs. The medium bandgap D-A conjugated polymer P consists of ethylhexylthiophene-2yl-1H-bisthieno[3,2-e:2'3'-g]benzothiazole donor unit and fluorinated benzothiadiazole acceptor unit.…”
Section: Doi: 101002/solr202100402mentioning
confidence: 99%
“…The small molecule donor (SMD) designed as D-A-D configuration consisting of difluroro-2,1-3-benzothiadiazole as the acceptor and dialkoxyphenyl-thiophene-based terminal donor units containing a lignin sourced phenol, guaiacol as the end groups. [55] This is used as third component in the P:Y6-based ternary OSCs. The medium bandgap D-A conjugated polymer P consists of ethylhexylthiophene-2yl-1H-bisthieno[3,2-e:2'3'-g]benzothiazole donor unit and fluorinated benzothiadiazole acceptor unit.…”
Section: Doi: 101002/solr202100402mentioning
confidence: 99%
“…8%. 8,9 Lastly, it would be impossible to list examples of biosourced key building blocks for organic electronics without mentioning furan. 10 Obtained from lignocellulose, this chalcogenophene has been widely associated with petroleumbased derivatives for the preparation of efficient donors in OPV 11 or p-type materials for OFETs 12 or OLEDs.…”
Section: A Introductionmentioning
confidence: 99%
“…Use of variation in the arrangement of the acceptor (A)–donor (D) units became popular in light-harvesting materials as they allow better intramolecular charge transfer from the acceptor to the donor units, leading to improved performance of the device. 24 Alternating arrangement of units as A–D–A was first introduced by Schulze et al 25 and found that the acceptor/donor interface assists the separation of excitons as electrons in the acceptor and holes in the donor. More recently, Chen et al 26 reported that A–D–A type acceptors exhibit outstanding performance with a PCE of 17.3% in tandem geometry.…”
Section: Introductionmentioning
confidence: 99%